Class II, Division 1 Angle malocclusion with severe proclination of maxillary incisors - Kátia Montanha (Dental Press Editora, 2016)
Protrusion of maxillary incisors is a common complaint among patients seeking orthodontic treatment. This report addresses the correction of Class II Angle malocclusion with excessively bucally proclined maxillary incisors, in an adolescent female patient, through the use of extraoral and fixed appliances. This case was presented to the Brazilian Board of Orthodontics and Dentofacial Orthopedics (BBO) as part of the requirements for obtaining the title of certified by the BBO.